2017
DOI: 10.14444/4007
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variations in Shear Strength and Density of the Human Thoracic Vertebral Endplate and Trabecular Bone

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The range of compressive strengths of the gyroid specimen were between 1.5 and 9.5 MPa and a shear strength of 0.3 and 3.2 MPa. Comparatively, the strength values of cancellous bone in literature were identified in the range of 5.1–6 MPa and a shear strength of 0.5–1.5 MPa 48–50 . The triangle and zig‐zag specimens would require a very low in‐fill density to replicate these features, which may compromise some of the structural properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The range of compressive strengths of the gyroid specimen were between 1.5 and 9.5 MPa and a shear strength of 0.3 and 3.2 MPa. Comparatively, the strength values of cancellous bone in literature were identified in the range of 5.1–6 MPa and a shear strength of 0.5–1.5 MPa 48–50 . The triangle and zig‐zag specimens would require a very low in‐fill density to replicate these features, which may compromise some of the structural properties.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reported compressive strength specifically in the cervical spine (Table 1 ). 45 , 46 , 47 , 48 , 49 , 50 However, no articles were found that identified the modulus of elasticity or shear strength of cancellous bone in the cervical spine. Therefore, lumbar spine properties were used as a close alternative.…”
Section: Methodsmentioning
confidence: 99%
“… 5 Recently, the localized BMD distribution has been widely studied and showed a strong association with bone strength and fracture risk. 24 , 27 , 28 , 29 Moreover, the focal osteoporosis defect observed in routine CT scans, which is a low‐resolution manifestation that correlated with focal microarchitecture changes, 3 has shown a positive association with the osteoporosis. 3 , 6 Nevertheless, most of the previous studies focused on the spatial distribution of the localized bone loss in sub‐regions, while merely quantified the actual structural properties of focal osteoporosis defects in routine CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sensitivity of the CT‐based bone density to the osteoporotic fracture risk is limited, 26 and it is widely believed that bone quality should also be considered for fracture risk analysis 5 . Recently, the localized BMD distribution has been widely studied and showed a strong association with bone strength and fracture risk 24,27–29 . Moreover, the focal osteoporosis defect observed in routine CT scans, which is a low‐resolution manifestation that correlated with focal microarchitecture changes, 3 has shown a positive association with the osteoporosis 3,6 .…”
Section: Discussionmentioning
confidence: 99%
“…According to anatomical studies of the vertebral endplates from the thoracic spine to the lumbar spine, the center to the anterior portion is the weakest region, while the posterolateral portion is the strongest [13,14]. Therefore, it is important to avoid an excessively large screw insertion angle in the axial direction and to insert the TSD along the axis of the pedicle as much as possible to enable the screw to hold the posterolateral portion of the vertebral endplate.In recent years, there have been increasing reports of the use of the posterior approach and PPSs for minimizing the surgical invasiveness.…”
Section: Discussionmentioning
confidence: 99%